(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND: The main aim to reconstruction of heel defect is weight bearing capability and sensory recovery. From different options, the choice of flap used depends on site and size of defect, donor area availability. OBJECTIVE: The objective of this article is to see the suitability of different loco-regional flaps for heel defects considering flap characteristics meeting the requirements of this critical weight bearing area. MATERIAL AND METHODS: Study design used is case series in which 20 patients having heel defects are included from July 2022 to July 2023 in which different flaps (medial planter artery flap, reverse sural flap, local random pattern flap) are used for the reconstruction. The outcome would be seen in terms of flap survival, recovery of sensation, the durability of coverage and function. Selection criteria: Inclusive criteria included patients with all heel defects, both genders, all ages, ambulant patients, While, exclusive criteria excluded patients that are bed ridden patients, poor life expectancy / outcome. Sampling method was convenience sampling. Data analysis was done using SPSS version 20. RESULTS: A total of 20 patients were taken in study 15 were males and 5 were female. Only 16 patients developed protective sensation, with a mean recovery time of 9.6 months (ranging from 8 to 14 months). Two cases of medial plantar artery flaps (used after tumor excision) and two cases of heel advancement flaps (used for posterior defects) demonstrated touch sensation at an average of 4.75 months (ranging from 11 to 12 months).The return of protective sensation and the mean AOFAS subjective score were notably higher in the non-neuropathic ulcer group. CONCLUSION: One of the common causes of heel defects especially in children in spoke wheel injury. To cover this defect locoregional flaps can be used with a satisfactory outcome. Among them reverse sural artery flap is a reliable option to cover most of the heel defects along with MPA depending upon the site of defect.